Analisis Kemampuan Membaca Lancar Siswa Kelas IV B di SD Negeri 99 Palembang - Permatasari, Intan; Akhbar, M. Taheri; Syaflin, Sylvia Lara (Institut Teknologi Pendidikan Indonesia, 2022)
The problem in this research is how the student's ability to read fluently in grade IV B SD N 99 Palembang. The purpose of this study was to determine the ability to read fluently in grade IV B SD N 99 Palembang. The research method used is the descriptive qualitative method. Data collection techniques used are interviews, observation, and documentation techniques. The data analysis technique used is data reduction, data presentation, and conclusion drawing. The research subjects in this study were students of class IVB SD Negeri 99 Palembang with a total of 20 students. The results in this study are the overallability to read fluently students obtained a percentage value of 90% which shows the high ability of students in reading fluently